2013
DOI: 10.1038/ncomms2796
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of asymmetric cell division and polarity by Scribble is not required for humoral immunity

Abstract: The production of protective antibody requires effective signalling of naive B cells following encounter with antigen, and the divergence of responding B lymphocytes into distinct lineages. Polarity proteins have recently been proposed as important mediators of both the initial B cell response, and potentially of asymmetric cell division. Here we show that, although polarity proteins of the Scribble complex, Scribble, Dlg1 and Lgl1, are expressed and polarized during early B cell activation, their deficiency h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 46 publications
5
79
0
Order By: Relevance
“…Many studies have shown, using knockdown approaches, that Scribble and Dlg play key roles in the response of T and B cells to antigen presentation Round et al 2005Round et al , 2007Humphries et al 2012;Ludford-Menting et al 2005;Xavier et al 2004). However, gene knockout studies have shown minimal and/or transient effects of deletion of Scribble, Lgl1, and Dlg1 on hematopoiesis and immune cell function Hawkins et al 2013Hawkins et al , 2014Humphries et al 2012;Heidel et al 2013). The discrepancy between knockdown and knockout studies is thought to reflect compensatory mechanisms by which lymphocytes might adjust to deletion of the Scribble module genes over time (Humphries et al 2012;Pham et al 2014), and further studies are required to resolve this discrepancy.…”
Section: The Immune Synapsementioning
confidence: 83%
“…Many studies have shown, using knockdown approaches, that Scribble and Dlg play key roles in the response of T and B cells to antigen presentation Round et al 2005Round et al , 2007Humphries et al 2012;Ludford-Menting et al 2005;Xavier et al 2004). However, gene knockout studies have shown minimal and/or transient effects of deletion of Scribble, Lgl1, and Dlg1 on hematopoiesis and immune cell function Hawkins et al 2013Hawkins et al , 2014Humphries et al 2012;Heidel et al 2013). The discrepancy between knockdown and knockout studies is thought to reflect compensatory mechanisms by which lymphocytes might adjust to deletion of the Scribble module genes over time (Humphries et al 2012;Pham et al 2014), and further studies are required to resolve this discrepancy.…”
Section: The Immune Synapsementioning
confidence: 83%
“…All lymphocytes were isolated from 8-to 16-week-old C57BL/6 mice. B cells were prepared, CFSE labelled and cultured as described 30,60 . Cell numbers were determined by reference to FACS calibration beads as described 29,31 .…”
Section: Methodsmentioning
confidence: 99%
“…We and others find a great deal of cell fate heterogeneity under simple in vitro culture conditions [4][5][6]12,13 . Conversely, crucial molecular contributors to early developmental programmes, including asymmetric cell division, do not alter B cell or T cell responses in vivo 14 . Thus, although the 3D environment and asymmetric programming might have some role in modifying cell fate allocation, they are not the only sources of variation.…”
Section: Reductionismmentioning
confidence: 97%